Kinerja UMKM melalui Kesadaran Ekonomi, Teknologi Keuangan, dan Ketahanan Keuangan di Kabupaten Bojonegoro - Muhammad Arung Nazarudin; Vidi Hadyarti (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the regional economy, including in Bojonegoro Regency. This study aims to examine the influence of economic awareness, financial technology, and financial resilience on the financial performance of MSMEs in Bojonegoro Regency. The population in this study were MSME actors, with a total of 144 respondents. The approach used was quantitative through primary data collection using questionnaires. Respondents were selected purposively, while data processing was carried out using the Structural Equation Modelling–Partial Least Squares and Regression methods using SmartPLS. The results of the analysis show that economic awareness, the use of financial technology, and financial resilience have a positive and significant effect on the financial performance of MSMEs. Simultaneously, these three variables were proven to contribute to improving the financial performance of MSMEs. These findings confirm that the ability of MSME players to understand economic conditions, optimise financial technology, and maintain business financial stability are key factors in improving financial performance in a sustainable manner.